Recent progress in block copolymer crystallization. Issue 4 (30th December 2018) - Van Horn, Ryan M.; Steffen, Maxwell R.; O'Connor, Dana
Abstract: Block copolymers (BCPs) are important for technological advances in numerous industries, including but not limited to, electronics, biomedical, optics, environmental, and infrastructure. Because of their ubiquity, it is important to understand their hierarchical phase behavior to tune their macroscopic properties for efficient use. These macroscopic properties are derived from the microscopic self‐assembled structures. One unique form of hierarchical assembly exists when one or more of the polymeric blocks form lamellar crystals. These crystals are integral to understanding and predicting the macroscopic behavior. This review reports on recent advances in crystallization of BCPs, including bulk and solution assembly. Reports highlighting development in fundamental processes regarding crystallization mechanisms and behavior as well as for the design of practical applications are included. Abstract : New technologies are being developed that require more precise and more diverse manufacturing. Block copolymers, or plastics, provide scientists and engineers with the ability to tailor structures on multiple length scales. Crystallization in these systems is important for the materials' properties such as strength, degradation rate, and conductivity, to name a few. This article summarizes recent work in the area of block copolymer crystallization.